Awake oral fibreoptic intubation with dexmedetomidine sedation in severe maxillofacial trauma following bear mauling: a case report - Xavier, Antony; Fernandez, Sandra (International Journal of Research in Medical Sciences, 2026)
Awake fibreoptic intubation (AFOI) is considered the gold standard for securing the anticipated difficult airway. Sedation should provide comfort while preserving spontaneous ventilation and airway reflexes, with dexmedetomidine offering cooperative and arousable sedation. A 57-year-old male from a hilly district in North-East India presented with extensive facial lacerations and near-mutilation following a bear attack. Following resuscitation and primary wound closure, he was posted for emergency left eye evisceration. Airway assessment revealed restricted mouth opening with an un-assessable Mallampati class, while associated bony injuries had not been excluded. Communication was severely limited by facial trauma and a language barrier, necessitating a trained translator. Anticipating difficult bag-mask ventilation and intubation, awake oral fibreoptic intubation under dexmedetomidine sedation with airway blocks was planned. After high-risk consent, dexmedetomidine was administered with a 50-µg bolus followed by 0.4 µg/kg/h infusion. Antisialagogue premedication and airway anaesthesia using glossopharyngeal, bilateral superior laryngeal and transtracheal lignocaine blocks were provided within recommended dose limits. Oral AFOI using an armoured endotracheal tube was successfully achieved on the second attempt. Anaesthesia was subsequently maintained with inhalational agents and intermittent vecuronium. After reversal with sugammadex, extubation was performed when the patient was fully awake and obeying commands. This case highlights the role of dexmedetomidine-assisted awake oral fibreoptic intubation with airway blocks in severe maxillofacial trauma when the nasal route is unsuitable, emphasizing meticulous consent, documentation and management of language barriers in emergency anaesthesia.